A Combination of Serum Biomarkers in Elderly Patients with Sarcopenia: A Cross-Sectional Observational Study. (21st February 2022) - Ying, Lin; Zhang, Qin; Yang, Yun-mei; Zhou, Jian-ying
Abstract : Background . The pathogenesis of sarcopenia in the elderly has not yet been fully understood. This study aimed to explore the relationship between sarcopenia and several serum biomarkers in elderly population. Methods . It was an observational cross‐sectional study of data collected from 70 patients. According to the criteria of the Asian Working Group for Sarcopenia (AWGS), subjects were divided into the sarcopenia group and nonsarcopenic group. We compared age, body mass index (BMI), biochemical indexes, smoking status, underlying disease, muscle mass, handgrip strength (HS), gait speed (GS), skinfold thickness, muscle thickness, and IL-6, IL-10, IL-17A, and TNF- α levels between these groups. Results . Of the 70 subjects, 35 patients were diagnosed with sarcopenia. The number of men was higher than that of women in both groups. The patients with sarcopenia were older and had lower BMI and muscle thickness but higher SARC-F questionnaire scores. However, the difference in smoking status and skinfold thickness between these two groups were not statistically significant. Higher IL-6, IL-17A, and TNF- α levels were observed in participants with sarcopenia P < 0.05 . Patients with sarcopenia had a lower IL-10 level. Positive associations were present between the severity of sarcopenia and IL-6, IL-17A, and TNF- α levels, while there was an inverse correlation between the presence of sarcopenia and IL-10 level. Conclusions . Our research found that in sarcopenic elderly subjects, the serum levels of several biomarkers, such as IL-6, IL-17A, and TNF- α, were higher than those in nonsarcopenic elderly persons. Further studies are needed to explore the possible molecular mechanisms and discover new therapeutic targets.